A proliferation‐inducing ligand–mediated anti‐inflammatory response of astrocytes in multiple sclerosis. Issue 3 (4th February 2019) - Baert, Laurie; Benkhoucha, Mahdia; Popa, Natalia; Ahmed, Mashal C.; Manfroi, Benoit; Boutonnat, Jean; Sturm, Nathalie; Raguenez, Gilda; Tessier, Marine; Casez, Olivier; Marignier, Romain; Ahmadi, Mitra; et al.
Abstract : Objective: The two related tumor necrosis factor members a proliferation‐inducing ligand (APRIL) and B‐cell activation factor (BAFF) are currently targeted in autoimmune diseases as B‐cell regulators. In multiple sclerosis (MS), combined APRIL/BAFF blockade led to unexpected exacerbated inflammation in the central nervous system (CNS) of patients. Here, we investigate the role of the APRIL/BAFF axis in the CNS. Methods: APRIL expression was analyzed in MS lesions by immunohistochemistry. The in vivo role of APRIL was assessed in the murine MS model, experimental autoimmune encephalitis (EAE). Functional in vitro studies were performed with human and mouse astrocytes. Results: APRIL was expressed in lesions from EAE. In its absence, the disease was worst. Lesions from MS patients also showed APRIL expression upon infiltration of macrophages. Notably, all the APRIL secreted by these macrophages specifically targeted astrocytes. The upregulation of chondroitin sulfate proteoglycan, sometimes bearing chondroitin sulfate of type E sugar moieties, binding APRIL, in reactive astrocytes explained the latter selectivity. Astrocytes responded to APRIL by producing a sufficient amount of IL‐10 to dampen antigen‐specific T‐cell proliferation and pathogenic cytokine secretion. Finally, an intraspinal delivery of recombinant APRIL before disease onset, shortly reduced EAE symptoms. Repeated intravenous injections of recombinant APRIL before and even at disease onset also had an effect. Interpretation: Our data show that APRIL mediates an anti‐inflammatory response from astrocytes in MS lesions. This protective activity is not shared with BAFF. ANN NEUROL 2019;85:406–420.